Orbital forcing and evolution of the Southern African Monsoon from late Miocene to early Pliocene - Azevedo, Allana Queiroz de (2024)
The late Miocene - early Pliocene (7.4 - 4.5 Ma) is a key interval in Earth’s history where intense reorganization of atmospheric and ocean circulation occurred within a global cooling scenario. The southern African monsoon (SAFM) potentially played an important role in climate systems variability during this interval. However, the dynamics of this important atmospheric system is poorly understood due to the scarcity of continuous records. Here, we present an exceptional continuous late Miocene to early Pliocene reconstruction of the SAFM based on elemental geochemistry (Ca/Ti and Si/K ratios), stable isotope geochemistry (δ18O and δ13C recorded in the planktonic foraminifera Orbulina universa), and marine sediment grain size data from the International Ocean Discovery Program (IODP) Site U1476 located at the entrance of the Mozambique Channel. Spectral characteristics of the Si/K ratio (fluvial input) was used to identify the main orbital forcing controlling the SAFM. Precession cycles governed precipitation from 7.4 to ~6.9 Ma and during the early Pliocene. From ~6.9 to 5.9 Ma, the precession and long eccentricity cycles drove the SAFM. The major Antarctic ice sheet expansion across this interval appear to influence the isotopic records of Orbulina universa imprinting its long-term variability signal as a response to the ocean and atmospheric reorganization. Precession cycles markedly weakened from 5.9 to 5.3 Ma, almost the same period when the Mediterranean Outflow Water ceased. These findings highlight important teleconnections among the SAFM, Mediterranean Sea, and other tropical regions.